2011
DOI: 10.1002/qua.22998
|View full text |Cite
|
Sign up to set email alerts
|

A DFT/TDDFT study of porphyrazines and phthalocyanine oxo‐titanium derivatives as potential dyes in solar cells

Abstract: Density functional theory and time dependent density functional theory calculations at the level of LDA/BP86/TZ2P were performed systematically on several Ti(IV) complexes of porphyrazines and one phthalocyanine. We performed an analysis of the frontier molecular orbitals of the ground state electronic structures and also discuss in particular the good concordance of our results with the experimental data, which affords to predict the geometrical and optical properties of new complexes (3, 4, and 7). We also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The results indicate that the best candidates of those investigated, and which exhibit appropriate anchoring groups, are the porphyrazine analogs of 1 along with complexes 2 and 3 (Scheme 2) [31].…”
Section: Figmentioning
confidence: 99%
“…The results indicate that the best candidates of those investigated, and which exhibit appropriate anchoring groups, are the porphyrazine analogs of 1 along with complexes 2 and 3 (Scheme 2) [31].…”
Section: Figmentioning
confidence: 99%
“…The systems with different peripheral substituents R are enumerated as follows: OH (1), C(CH 3 ) 3 (2), 18 CH 3 (3), C 6 H 5 (4), H (5), CO 2 H (6), NO 2 (7), and  PO 3 H 2 (8). In addition, we studied the complexes with R =  C(CH 3 ) 3 , changing B and including over the Pz ring the  CO 2 H anchoring group.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Porphyrins and phthalocyanines are targets of interest in areas such as photocatalysis, catalysis, and energy conversion devices, among others. For these reasons, considerable efforts have been made to synthesize new structures that might show improved molecular properties. In addition, theoretical studies have been performed to better understand the optical, electronic, and magnetic properties of metal-free complexes, coordinated to metals (such as Zn, Ni, Co, Ti, Ru, and Al) and also dimers of these macrocycles linked by bridges. Moreover, attention has been focused on the formation of ordered thin-film assemblies, such as those constituted by dimers or heterodimers of porphyrins (P), porphyrazines (Pz), and phthalocyanines (Ph) connected by different bridges/linker groups including benzene ring, naphthalene ring, or mutual chelation of a metallic ion. Some bridges help to keep rigid coplanar configurations of the systems, which generally exhibit spectroscopic and electrochemical properties that occasionally are significantly different from those of their monomer parents. Among their applications, these macrocycles are considered to be excellent sensitizers in the design of dye-sensitized solar cells (DSSCs), because of its good performance in light-harvesting devices. DSSCs are mainly composed of nanocrystalline films of semiconductor oxides with wide band gaps (i.e., TiO 2 and ZnO) and a layer of dye attached to this semiconductor surface.…”
Section: Introductionmentioning
confidence: 99%
“…29,32,33 Furthermore, Pz have also been of interest to theoretical chemists. [34][35][36][37] Lelj et al investigated the electronic structure of peripherally unhindered Pz using a density functional approach and showed that peripheral substituents yield modications to the "core" of the macrocycle and to the energy levels, changing s and p interactions. 34 Arratia-Pérez et al studied several Ti(IV) complexes of Pz and one phthalocyanine using density functional theory and time dependent density functional theory calculations at the level of LDA/BP86/TZ2P.…”
Section: Introductionmentioning
confidence: 99%
“…34 Arratia-Pérez et al studied several Ti(IV) complexes of Pz and one phthalocyanine using density functional theory and time dependent density functional theory calculations at the level of LDA/BP86/TZ2P. 36 They suggested that three Ti-Pz complexes could act as lightharvesting sensitizers for DSSCs. Recently, Su et al have performed a detailed TDDFT analysis on the ground-state structures and the absorption spectra of tetrathiafulvaleneannulated ZnPz, and suggested it as a candidate for DSSCs due to the broad and intense red-shied Q band.…”
Section: Introductionmentioning
confidence: 99%